Understanding transport mode choice for commuting: the role of affect. Issue 4 (18th May 2020) - Ababio-Donkor, Augustus; Saleh, Wafaa; Fonzone, Achille
ABSTRACT: This study examines the relationship between positive and negative user valence and transport mode choice behaviour. We integrate latent attitudes ' affect' and ' salience' into transport mode choice models using the framework of integrated choice and latent variable modelling and simultaneous maximum likelihood estimation methods. The results are consistent with findings in similar travel behaviour and behavioural economics literature. The study extends the findings of previous research and has demonstrated that user sentiments about public transport mode and salient public transport experiences have a significant impact on travel mode choice behaviour. It was found that private motorised users are more sensitive to overcrowding and anti-social behaviours on PT than active and PT travellers. Key attitudinal indicators influencing individual transport choice behaviour are established to guide public policy. The key indicators of Affect and Salience must be analysed and addressed through public policy to enhance PT user experience and develop services and facilities to increase the utility of PT in-vehicle travel time.